PROBLEM ISSUES OF ACCOUNTING OF NON-PROFIT ORGANIZATIONS - TROSTIANSKA, KARYNA; KRYZHANOVSKA, OLGA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article is devoted to the study of problematic issues of accounting of non-profit organizations. The role of the non-profit sector in the socio-economic life of society was determined and the peculiarities of accounting of such organizations were considered. As the non-profit sector plays an important role in the socio-economic life of society, provides an increase in living standards, sustainable development of the country. In the conditions of modern transformations, the society needs the existence of organizations, different from the subjects of entrepreneurial activity, which will solve social problems at a qualitatively new level. Accordingly, non-profit organizations that have a positive economic and social impact on the development of a market-oriented and democratic society in the world’s leading countries must function properly in the national economy. Accounting is the basis of effective management of a non-profit organization in modern conditions. That is why the study of the features and procedures of accounting for their activities is extremely relevant, given the importance of their contribution to the socio-economic development of the state. The latest recommendations of regulations, tax authorities and industry specialists are analyzed and our own view on the specifics of accounting by non-profit organizations is given. It was found that the methodology of accounting of non-profit organizations is one of the most acute problems of accounting reform. The main problems are related to the accounting of targeted funding and their use, accounting for inventories, fixed assets and their depreciation. To address such issues, it is proposed to make a number of changes and additions to the existing accounting methodology, which will achieve a reliable display of accounting information for effective management decisions.